Membangun Budaya Keselamatan Kerja melalui Partisipasi Sosial untuk Memperkuat Kesadaran Kewarganegaraan - Rahayu, Yayuk Muji; Kurniati, Pat (DAS Institute, 2025)
The high number of work accidents caused by low worker participation in safety initiatives indicates that the implementation of work safety culture in various sectors is not optimal. This study aims to analyze the role of social participation in strengthening work safety culture while increasing workers' citizenship awareness. Using a qualitative descriptive method based on literature study, this study examines relevant literature related to work safety culture, social participation, and citizenship awareness. The results of the study indicate that social participation, through worker involvement in training, discussions, and decision-making related to safety, can increase solidarity, collective responsibility, and compliance with safety protocols. This has an impact on reducing the risk of work accidents and creating a safer, more productive, and more collaborative work environment. The conclusion of this study confirms that the integration of social participation in work safety culture not only reduces work risks but also internalizes citizenship values in workers, which contributes to organizational sustainability. The prospect of implementing these findings can be an effective strategy in creating a sustainable work safety culture based on collective values in various sectors.